Convalescent plasma for COVID-19 complicated by ARDS due to TRALI. Issue 1 (28th January 2021) - Wang, Kevin Y; Shah, Pratik; Pierce, Matthew
Abstract : Convalescent plasma, which contains antibodies from recovered individuals, has been used as an effective treatment for infectious diseases in the past and is currently being used as a potential treatment option for COVID-19. Multiple studies have reported this treatment to be safe. We report a case of a patient who developed acute respiratory distress syndrome (ARDS) with features suggestive of transfusion-related acute lung injury after being treated with convalescent plasma for COVID-19. We emphasise the need to be aware of the potential risk of transfusion reactions and disease worsening with convalescent plasma administration and to weigh the risk and benefits of this therapy before administration to patients and propose that further study be done regarding the potential risks of convalescent plasma.